2017
DOI: 10.1039/c7cp05793h
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of halogen atoms and molecules with borophene

Abstract: The realization of buckled monolayer sheets of boron (i.e., borophene) and its other polymorphs has attracted significant interest in the field of two-dimensional systems. Motivated by borophene's tendency to donate electrons, we analyzed the interaction of single halogen atoms (F, Cl, Br, I) with borophene. The possible adsorption sites are tested and the top of the boron atom is found as the ground state configuration. The nature of bonding and strong chemical interaction is revealed by using projected densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 66 publications
9
24
0
Order By: Relevance
“…In our previous study, by taking a large 7 × 4 supercell (with lattice parameters of 11.30 and 11.45 Å), we showed that F strongly binds to the borophene surface and the top of the B atom on the upper layer (T-site) is the most favorable adsorption site. 43 The obtained energy barriers along the diffusion paths are very high (1.26 eV along a and 0.84 eV along b ), indicating low possibility of migration. Moreover, F 2 dissociates spontaneously without an activation barrier on the borophene surface, suggesting that adsorption of F is an exothermic process.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In our previous study, by taking a large 7 × 4 supercell (with lattice parameters of 11.30 and 11.45 Å), we showed that F strongly binds to the borophene surface and the top of the B atom on the upper layer (T-site) is the most favorable adsorption site. 43 The obtained energy barriers along the diffusion paths are very high (1.26 eV along a and 0.84 eV along b ), indicating low possibility of migration. Moreover, F 2 dissociates spontaneously without an activation barrier on the borophene surface, suggesting that adsorption of F is an exothermic process.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, the interaction with halogen atoms not only modifies the intrinsic properties of borophene but can also enhances the stability by the occupation of out-of-plane bonding states. Despite its importance, to the best of our knowledge, only the interaction of single halogen atoms/molecules with borophene is studied, 43 and halogenation has not been explored yet. With this motivation, in this work, we investigate the possible fluorinated derivatives of borophene and analyze the mechanical, electronic, and thermal properties of the stable systems by using ab initio methods.…”
Section: Introductionmentioning
confidence: 99%
“…Even though experimentally not yet realized, fluorinated borophene structures with varying coverage concentrations have been also foreseen. 62,63 Interestingly, while fully fluorinated borophene (BF) was not found to be stable, single-sided coverage with 25% fluorination (B 4 F) and double-sided coverage with 50% fluorination (B 2 F) were shown to be dynamically stable. 62 The structures of B 4 F and B 2 F which can be realized by using 2 Â 1 and 2 Â 2 super cells of pristine borophene, respectively, are shown in Fig.…”
Section: B the Effect Of Functionalizationmentioning
confidence: 99%
“…All these structures can show different behaviors under similar compression and torsion forces with Borophene surfaces are very different from those observables on graphene; in fact, borophene has ridges with a morphology that strongly depends on how deep the boron atoms bind together. These structural features make borophene a polymorphous and anisotropic material [6].…”
Section: Main Properties Of Borophenementioning
confidence: 99%